Statistical methods in quantum optics 2 : non-classical fields - Carmichael, Howard J. (Springer, 2017)
The Degenerate Parametric Oscillator I: Squeezed States -- The Degenerate Parametric Oscillator II: Phase-Space Analysis in the Small-Noise Limit -- The PositivePRepresentation